Determining Factors of Audit Delay of Large Trading Companies on the Indonesia Stock Exchange - Astuti (International Journal of Science, Technology & Management, 2021)
Financial statements delivered in a timely manner are useful in analyzing and making decisions in the economic field that can contribute to national economic growth. The timeliness of a financial statements on the results of the audit report can also affect the value of the financial statements. This research aims to find out and analyze the effect of leverage, company size and company age on audit delay. The conduct of the research was conducted on twenty Large Trading Companies during the period 2015-2019 which totaled 100 data. The data analysis techniques used in this research are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that partially leverage had a positive and insignificant effect on audit delay, the company size had a negative and insignificant effect on audit delay, while the company age had a negative and significant effect on audit delay.